Biomarcadores sanguíneos para a doença de Alzheimer : avaliação da expressão gênica da ADAM10 e de micro- RNAs - Moralles, Patricia Regina Manzine (Universidade Federal de São Carlos, 2016)
ADAM10 is an-secretase that cleaves APP in the non-amyloidogenic pathway, thereby inhibiting -amyloid peptide (A ) production in Alzheimer´s disease (AD). Studies have shown decreased ADAM10 platelet levels in AD patients as well as the deregulation of microRNAs (miRNAs) related to molecules involved in the pathophysiology of this disease. The objective was to verify and compare ADAM10 gene expression and micro-RNAs (miRNAs) between AD patients and controls without cognitive impairment. It is a comparative study, based on the assumptions of quantitative research. Biological samples were collected, analyzed and stored in a biorepository. The ADAM10 gene expression in whole blood was studied in 47 AD, 32 healthy controls and 21 mild cognitive impairment (MCI) subjects by RT-qPCR techniques and analyzed by relative expression by 2- Ct. For miRNAs analyses, using MegaplexTM and MirWalk 2.0 database, were analyzed by RT-qPCR ~700 miRNAs in total blood and 21 miRNAs of them were validated in a sample of 21 AD subjects and 17 healthy controls. Statistical association tests, regression and diagnostic accuracy were performed. No significant differences in ADAM10 gene expression were observed between AD and control groups. Therefore, the decrease of ADAM10 protein in platelets of AD patients was not caused by a reduction in mRNA encoding for ADAM10. Mir-144-5p, miR-374 and miR-221 were downregulated in AD subjects, with moderate accuracy diagnosis. However, the association of selected miRNAs expression and Mini Mental State Examination (MMSE) was significantly better as a diagnostic tool compared to their expression separately. The validated miRNAs are involved in the regulation of pathways related to neurodegenerative diseases (beta-amyloid cascade, ubiquitination, transcriptional regulator, synaptic transmission, vesicle trafficking). Specifically, miR-144-5p, miR-374 and miR-221 are relevant for AD, as regulators of APP, BACE1 and ADAM10 translation. To the best of our knowledge, this is the first study to demonstrate a downregulation of these specific miRNAs in total blood of Alzheimer’s disease patients, compared to healthy cognitive controls. These findings are in agreement with AD protein outcomes and place the miRNAs evaluated as potential biomarkers that can be used to improve AD diagnosis.
Keywords: Idoso; Doença de Alzheimer; Biomarcadores; ADAM10; RT-qPCR; miRNA; Sangue total; Elderly; Alzheimer´s disease; Biomarkers; ADAM10; RT-qPCR; miRNAs; Total blood; CIENCIAS BIOLOGICAS